Remodeling of cortical and corticocancellous fresh-frozen allogeneic block bone grafts - a radiographic and histomorphometric comparison to autologous bone grafts - Spin Neto, Rubens; Stavropoulos, Andreas; Coletti, Felipe L. [UNESP]; Pereira, Luís A. V. D.; Marcantonio Júnior, Elcio [UNESP]; Wenzel, Ann (Wiley, 2014)
Objectives: To compare cortical (AL-C) and corticocancellous (AL-CC) fresh-frozen block bone allografts to cortical block bone autografts (AT) used for lateral ridge augmentation in terms of radiographic dimensional maintenance and histomorphometrical graft remodeling. Materials and methods: Twenty-four patients, requiring ridge augmentation in the anterior maxilla prior to implant placement, were treated with AT, AL-C or AL-CC bone blocks (eight patients per graft type). Patients were examined with CBCT prior to, 14 days, and 6–8 months after grafting. Amount of augmentation and dimensional block graft maintenance over time was evaluated by comparing planimetric measurements of the alveolar ridge made on CBCT sections of the augmentation area. During implant installation surgery, 6–8 months after grafting, cylindrical biopsies were harvested perpendicularly to the lateral aspect of the augmented alveolar ridge. The relative volumes of vital and necrotic bone and soft tissues were histomorphometrically estimated. Comparisons among groups and observation times were performed using Friedman test followed by Dunn’s post-hoc test. Results: Radiographic evaluation showed that the three types of grafts resulted in a significant increase in alveolar ridge width, with no significant differences among the groups in terms of ridge dimensions at the various observation times. However, significant graft resorption (P = 0.03) was observed in the AL-CC group over time (8.3 7.1%) compared with the AT and AL-C groups, where a slight increase was observed, on average (1.5 20.6% and 1.3 14.9%, respectively). Histomorphometrical analysis showed that larger amounts of vital bone were found in the biopsies from the AT augmented sites (25.1 11.2%) compared with AL-CC and AL-C augmented sites (9.3 3.8% and 3.9 4.6%, respectively; P ≤ 0.01). AL-CC and AT biopsies had the smallest amount of necrotic bone (38.2 12.1% and 56.7 26.0, respectively) compared with AL-C (83.7 10.8%, P < 0.01) biopsies. AL-CC biopsies showed the largest amount of soft tissues (52.5 11.7%) compared with those from AT (18.1 17.1%, P = 0.03) and AL-C (12.3 8.5%, P < 0.01) sites. Conclusions: AL block bone graft architecture influences significantly its dimensional incorporation and remodeling. Compared with AT bone graft, a small portion of the AL block consists of vital bone 6–8 months after grafting. Cortical AL blocks seem to show the least amounts of vital bone, while corticocancellous AL blocks seem to undergo more resorption over time. Among the
Keywords: Autogenous bone; Bone augmentation; Fresh-frozen allogeneic bone; Histology; Human; Osseointegration